2020
DOI: 10.3390/pr8060642
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interpretation of Pharmaceuticals’ Adsorption on Carbon Nanomaterials: Theory Meets Experiments

Abstract: The ability of carbon-based nanomaterials (CNM) to interact with a variety of pharmaceutical drugs can be exploited in many applications. In particular, they have been studied both as carriers for in vivo drug delivery and as sorbents for the treatment of water polluted by pharmaceuticals. In recent years, the large number of experimental studies was also assisted by computational work as a tool to provide understanding at molecular level of structural and thermodynamic aspects of adsorption processes. Quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 320 publications
0
17
0
Order By: Relevance
“…The best system for DOX encapsulation in Hk2 chiral nanotubes is therefore Ch(13,08)0N-HK2-DoxDIn.v1 (run 1, Table 2 ) with the DOX in the defect region and v1 orientation (with the nitrogen pointing towards the center of the nanotube). In this conformation, the formation of the non-covalent DOX-CNT interactions is facilitated, which are mainly constituted by π–π stacking interactions complemented by NH-π, CH-π, C=O-π and van der Waals interactions [ 20 , 31 , 46 ]. Figure 6 shows the non-covalent interactions for the most favorable case with the DOX in the area of the nanotube defect (a large green surface is observed) and as a comparison, the same nanotube with the DOX encapsulated in the regular area (less green regions and more red regions are observed), with PB DOX-CNT binding energy values of −109 and −80 kcal/mol, respectively (runs 1 and 3, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The best system for DOX encapsulation in Hk2 chiral nanotubes is therefore Ch(13,08)0N-HK2-DoxDIn.v1 (run 1, Table 2 ) with the DOX in the defect region and v1 orientation (with the nitrogen pointing towards the center of the nanotube). In this conformation, the formation of the non-covalent DOX-CNT interactions is facilitated, which are mainly constituted by π–π stacking interactions complemented by NH-π, CH-π, C=O-π and van der Waals interactions [ 20 , 31 , 46 ]. Figure 6 shows the non-covalent interactions for the most favorable case with the DOX in the area of the nanotube defect (a large green surface is observed) and as a comparison, the same nanotube with the DOX encapsulated in the regular area (less green regions and more red regions are observed), with PB DOX-CNT binding energy values of −109 and −80 kcal/mol, respectively (runs 1 and 3, Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, EPO is usually taken intravenously, but due to its sensitivity to intestinal enzymes, its activity will drop rapidly. When EPO is adsorbed by carbon nanomaterials, pharmacokinetic studies have shown that the biological activity of EPO is increased by 4 times [17,18]. Generally speaking, a nonlinear inhibition model is used to analyze the relationship between drug concentration and the effect of the target site in the body:…”
Section: Medical Application Research Of Fullerene Nanomaterialsmentioning
confidence: 99%
“…Recently, Serrano-Aroca et al [ 10 ] have proposed to use carbon-based nanomaterial against COVID-19. Regarding the chemistry of graphene and its derivative, the existence of functional groups, such as carboxylic acid (COOH), hydroxyls (OH), and epoxides (COC), on its surface, especially in graphene oxide (GO) and reduced graphene oxide (rGO), allows graphene to be coupled to different biomolecules, expanding the diversity of its biomedical applications [ 11 14 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%